High Temperature Deformation and Microstructural Features of TXA321 Magnesium Alloy: Correlations with Processing Map1. Issue 8 (3rd April 2013) - Dharmendra, Chalasani; Rao, Kamineni Pitcheswara; Prasad, Yellapregada Venkata Rama Krishna; Hort, Norbert; Kainer, Karl Ulrich
Abstract The hot deformation of cast TXA321 alloy has been studied in the temperature range 300–500 °C and in the strain rate range 0.0003–10 s−1 by developing a processing map. The map exhibited four domains in the temperature and strain rate ranges: (1) 300–325 °C and 0.0003–0.001 s−1, (2) 325–430 °C and 0.001–0.04 s−1, (3) 430–500 °C and 0.01–0.5 s−1, and (4) 430–500 °C and 0.0003–0.002 s−1. The first three domains represent dynamic recrystallization, resulting in finer grain sizes in the first two domains and coarser in the third domain. In the fourth domain, the alloy exhibited grain boundary sliding resulting in intercrystalline cracking in tension and is not useful for its hot working. Two regimes of flow instability were identified at higher strain rates, one at temperatures <380 °C and the other at >480 °C.